1986
DOI: 10.1055/s-2008-1025739
|View full text |Cite
|
Sign up to set email alerts
|

Renal Responses to Bicycle Exercise in Trained Athletes: Influence of Exercise Intensity

Abstract: The effects of exercise on renal function were studied in 11 male bicyclists, using a bicycle ergometer. At a work intensity of 100/150 W, bicycle exercise for 1 h was associated with a significant increase in urine volume, endogenous creatinine clearance, and renal sodium and potassium excretion. In contrast, exercise of the same duration at a work intensity of 150/200 W produced no significant changes in the above variables. Exercise intensity seems to influence renal responses, presumably through a differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Calculated values for sCr MDRD, sCr CKD-EPI, and eGFR sCr/CyC significantly decreased over the pre-exercise to 1 h post-exercise time period, which coincides with changes observed in sCr concentrations post-exercise. The results are consistent with previous studies that observed decreases in eGFR when using sCr as the indirect biomarker to assess renal filtration in healthy populations [4,[32][33][34]40,41]. Consequently, the aforementioned research studies noted that the greatest changes in sCr and eGFR are mainly due to the intensity and length of the exercise session that activates a more significant amount of skeletal muscle catabolism [32,36,40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Calculated values for sCr MDRD, sCr CKD-EPI, and eGFR sCr/CyC significantly decreased over the pre-exercise to 1 h post-exercise time period, which coincides with changes observed in sCr concentrations post-exercise. The results are consistent with previous studies that observed decreases in eGFR when using sCr as the indirect biomarker to assess renal filtration in healthy populations [4,[32][33][34]40,41]. Consequently, the aforementioned research studies noted that the greatest changes in sCr and eGFR are mainly due to the intensity and length of the exercise session that activates a more significant amount of skeletal muscle catabolism [32,36,40].…”
Section: Discussionsupporting
confidence: 91%
“…Conventional biomarker sCr transiently increased 1 h post-exercise (Figure 2). This finding is similar to the current literature on aerobic exercise and sCr [32][33][34]. However, the mode of exercise is different; thus, a direct comparison between previous studies cannot be fully elucidated.…”
Section: Discussionsupporting
confidence: 89%
“…the climatic and environmental conditions, the athletes physical shape and not least the mode and duration of exercise. Hence, both improved and altered renal functions have been reported for the various sports [3,13,24,27,28]. Particularly the duration of exercise exerts a crucial impact on volume status and renal function due to their tight physiological interdependence [22].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in UF and U N~~~ accompanying exercise vary with exercise intensity. For example, increases in UF and UNAex have been observed during low intensity exercise in man (Kachadorian and Johnson 1970;Virvidakis et al 1986;Freund et al 1991) and the horse (McKeever et al 1991) while more intense exercise leads to decreases in UF and UNAex in both species (Kachadorian and Johnson 1970;Poortmans 1984;Zambraski 1990;Freund et al 1991;Schott et al 1991a). Therefore, the tendency for UF to increase during the warm-up in this study was consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%